Experimental analysis of transient and steady-state heat transfer from an impinging jet to a moving plate - Kistak, Celal; Taskiran, Ali; Celik, Nevin (Springer, 2024)
In this study, the transient and steady-state heat transfer caused by an air jet impinging on a heated plate moving back and forth in the horizontal direction is investigated experimentally. The jet flow issuing form nozzle of various geometry (circular, triangle, square) is impinged on rough and smooth surfaces. In addition, Reynolds number (jet velocity), distance between the nozzle and the plate, plate velocity and stroke are considered as independent parameters that could affect the heat transfer.The optimum number of experiments is determined with the help of Taguchi design of experiment method. The transient and steady-state heat transfer are analyzed by means a high-technology thermal camera. Local and average Nusselt numbers representing the heat transfer characteristics are calculated in response to the variable parameters. Comparative graphs and ANOVA test results are presented and evaluated in order to determine the effects of parameters on heat transfer. As a result, it has been seen that Reynolds number (82%) is the most dominant parameter affecting heat transfer. Other parameters are listed as nozzle geometry (7.6%), surface roughness (4.9%), plate velocity (1%), stroke (0.6%) and nozzle-plate distance (0.1%) according to their degree of effect.
Keywords: Impingement; Velocity; Surface